Wanita Haid dengan Metode Syarah Perspektif Teologi Islam - Siti Rahmah (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the sharah about the hadith of menstruating women from a theological perspective. This research is a qualitative type through literature study with the method of sharah and theological analysis. The results and discussion of this study include the meaning of menstruation, syarah about the hadith of menstruating women, and the problems of menstruating women with theological perspective. This research concludes that theologically menstruating women according to the hadith sharah can still maintain a relationship with Allah through practices such as charity, doing good deeds, reciting the Qur'an, praying, doing istighfar, and reciting zikr. This study recommends especially for Islamic religious extension workers to be able to provide understanding to Muslim audiences about the sharah about the hadith of menstruating women from a theological perspective.